Pseudomonas populations causing pith necrosis of tomato and pepper in Argentina are highly diverse - Alippi, Adriana Mónica (2003)
Pseudomonas species causing pith necrosis symptoms on tomato and pepper collected in different areas of Argentina were identified as Pseudomonas corrugata, P. viridiflava and Pseudomonas spp. Their diversity was analysed and compared with reference strains on the basis of their phenotypic characteristics, copper and antibiotic sensitivity tests, serology, pathogenicity, DNA fingerprinting and restriction fragment length polymorphism (RFLP) analysis of a 16S rRNA gene fragment. All P. corrugata strains tested were copper-resistant while P. viridiflava strains were more variable. Numerical analysis of phenotypic data showed that all P. corrugata strains formed a single phenon that clustered at a level of about 93%, while all the P. viridiflava strains clustered in a separated phenon at a level of 94%. Genomic analysis by repetitive (rep)-PCR and 16S rRNA-RFLP fingerprinting and serological analysis showed that the two species contained considerable genetic diversity. Inoculations of tomato and pepper plants with strains from both hosts caused similar pith necrosis symptoms. Strains of both P. corrugata and P. viridiflava were grouped according to their geographical origin and not according to the original host. This is the first report of Pseudomonas viridiflava causing pith necrosis on pepper.